Campaña comunicativa para fomentar el turismo interno y externo del cantón Guano - Villacrés Ramos, María Cristina (2014)
According to information provided by the Guano Municipality, there have been no previous Communications Campaigns to promote tourism. Along this premise, a plan has been developed for the design of a "Communication Campaign to promote the internal and external tourism for the Guano town" for which an investigation and analysis of compiled information resulted in the proposal of various communications strategies which allow for the development of tourism and the town. The study and tourist analysis completed in Guano has allowed for an assessment of the current situation, and established the best communication strategies with the goal of attracting national and international tourists to visit the canton and learn more about the area. During the development of the thesis, the strengths and weaknesses associated with the area can be identified, the points of interest for tourists can be detailed, the tourism potential for the canton can be maximized, and new streams of revenue can be generated for the development of the area. In the same manner it will be possible to visualize the concept of the national and foreign tourist with respect to tourism.